Increase in contact lens use by water polo players due to a change in product quality: A 20-year study of Japanese college players - Komori, Y.; Kobayashi, D.; Murase, Y.; Enomoto, I.; Takagi, H.; Kono, I. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Water polo is a heavy contact team sport, which is why it is also regarded as rugby football being played in water. According to the rules of water polo, players shall remove any articles likely to cause injury before taking part in a game. Therefore, wearing eyeglasses or swimming goggles is prohibited in principle. This rule forces players with low visual acuity to use contact lenses during play. However, the consequences of contact lens use by water polo players have not been reported. The purpose of this study was to investigate contact lens use by competitive water polo players from Japanese colleges in 1991, 1996, 2001, 2006, and 2011. Methods: We investigated the following 5 groups of male water polo players from Japanese colleges: a group of 114 players in 1991, 118 players in 1996, 121 players in 2001, 118 players in 2006, and 130 players in 2011. Information about the use of contact lenses during play, the different types of contact lenses, and any previous cases of ophthalmopathy was obtained through a self-report questionnaire. Results: Fifty-four percent of the players were using contact lenses during water polo play in 1991 (p < 0.01); more than 74% in 1996; 89% in 2001; 84% in 2006; and 86% in 2011. While 96% of the contact lenses used by the players in 1991 were soft type (SCL), 74%, 92%, 86%, and 88% of the contact lenses used in 1996, 2001, 2006, and 2011, respectively, were disposable type (DSCL). The problem was that the players using contact lenses during play had sustained significantly higher corneal and conjunctival damage than players using vision correction devices in their daily lives and players without vision correction devices (p < 0.01). Conclusions: These findings demonstrate that a high percentage of players were using vision correction devices while playing water polo between 1996 and 2011. This may be correlated with the fact that many players were DSCL users. DSCL is currently considered the optimal vision correction device for water polo players. This study suggested that increasing contact lens use for water polo players may induce beneficial effects in terms of maintaining good vision.